Peningkatan Hasil Belajar Pendidikan Agama Islam Siswa Tunagrahita Kelas VII Melalui Metode Kelompok Materi Shalat - Hadisa Nadia; Ayundari Cahyani; Safika; Putra, Purniadi (CV Putra Publisher, 2024)
The main strategy for increasing teacher professional competence and student academic achievement is to carry out PTK using qualitative methodology. To gain a comprehensive understanding, researchers observed student learning activities, teacher learning activities, and student learning achievement tests. By prioritizing achieving classical learning completeness above 75%, this research guarantees objectivity in the teaching process and does not involve third parties. Tests, observations, interviews and group discussions are some of the methods used to collect data, which is then analyzed descriptively using the percentage method. Learning outcomes are assessed by comparing student performance on the first exam and the final exam. On the other hand, student actions are categorized as active or inactive. Discussion topics include PAI, prayer material, group work methods, student characteristics, and data on the initial abilities and learning outcomes of seventh grade mentally retarded students at SLBN Sambas. With a focus on inclusive education, this research highlights the importance of special approaches to learning for students with intellectual disabilities to support their development.